2018
DOI: 10.4103/ijdr.ijdr_602_16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the fracture resistance of premolars with extensive and medium cavity preparations restored with direct restoring systems

Abstract: The cavity preparation weakens the remaining tooth structure; however, its resistance could be partially restored using direct adhesive restorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Deep gingival floors of the proximal boxes which could act as a fulcrum for cusp bending in conjunction with decreased thickness might lead to lower fracture strength in extended preparations [ 30 ]. Another study by Pottemaier et al [ 31 ] showed that increasing the cavity width from 1/3 of the intercuspal distance to 2/3 did not decrease the fracture strength.…”
Section: Discussionmentioning
confidence: 99%
“…Deep gingival floors of the proximal boxes which could act as a fulcrum for cusp bending in conjunction with decreased thickness might lead to lower fracture strength in extended preparations [ 30 ]. Another study by Pottemaier et al [ 31 ] showed that increasing the cavity width from 1/3 of the intercuspal distance to 2/3 did not decrease the fracture strength.…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributed to the presence of a continuous circle of dental structure composed from buccal and lingual cusps and intact marginal ridges. While the teeth with Class-II MOD cavity undergo a greater reduction in fracture resistance as a result of the damage at the marginal ridge, which weakens the residual tooth structure and increases their susceptibility to fracture [ 20 22 ]. This came in general agreement with other studies which reported that the intact teeth displayed a greater value of FR when compared to the prepared unrestored teeth [ 5 , 20 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the teeth with Class-II MOD cavity undergo a greater reduction in fracture resistance as a result of the damage at the marginal ridge, which weakens the residual tooth structure and increases their susceptibility to fracture [20][21][22]. is came in general agreement with other studies which reported that the intact teeth displayed a greater value of FR when compared to the prepared unrestored teeth [5,20,23,24]. e second null hypothesis, which stated that there would be nonsignificant difference in FR value of premolar restored with bulk-fill restorative materials and that incrementally restored with conventional composite was accepted.…”
Section: Discussionmentioning
confidence: 99%
“…15 The negative control (prepared unrestored teeth) group, on the other hand, had the lowest FR values, which might be related to the MOD cavity preparation's weakening impact as a result of the damage at the marginal ridge, which weakens the residual tooth structure. 35 Amongst the restored groups, Aura BF group showed the highest FR values with no significant difference with the conventional Filtek Z350 XT restored group. This result might be attributed to the high filler loading (81% and 78.5%) respectively.…”
Section: P1: Comparison Between Aura Bf and Other Groups P2: Comparis...mentioning
confidence: 84%